Prenatal Study of Testes Growth and Histological Development 2-Fetal Goat: Amin,F.A.S.M. ; Alwan A.F. - S.M, Amin F.A. (The Iraqi Journal of Veterinary Medicine, 2010)
This study was conducted on 53 samples of female local Kurdi goats uterus contained one or two fetuses .These samples were collected from Sulaimani slaughter house, A total of 53genitlia were consisted of 36 (67.92%)single and 17(32.08%)twin fetuses ,with a total of 70 fetus,of them 33(47.14%) and 37(52. 86%) were located in the right and left horns, respectively. The number of fetuses with macroscopically clear external sex organ was 55, the total number of male fetuses was 34(48.57%) while the female was 21(30%).The fetuses whose external organ could not be diagnosed were 15(21.42%). The weight of the fetal testes and the length of scrotum were increased steadily with an increasing in the fetal Crown Rump Length(CRL). When the CRL is 2.5-5cm testes location is close to the kidney, while testes are located in the inguinal ring and/or scrotum at about20-23 and 28cm.Histological sections of testes showed the density of fibroblast layer and connective tissue capsules as well as the appearance of seminiferous tubles containing a few spermatogonia cells and small leydig cells at early stages of CRL=8cm. With an increasing in CRL , the seminiferous tubules filled with different types of spermatogonia cells, spermatocytes cells ,increasing in number and size of sertoli and leydig cells. Different Types of spermatid were also present in sections of more than 20cm CRL. The study indicated that the fetal testes secreted testosterone hormone which is essential for testes development and descending